Intersphincteric resection for low rectal cancer: the risk is functional rather than oncological. A 25‐year experience from Bordeaux. (5th September 2020) - Denost, Q.; Moreau, J.‐B.; Vendrely, V.; Celerier, B.; Rullier, A.; Assenat, V.; Rullier, E.
Abstract: Aim: There are few data evaluating the long‐term outcomes of intersphincteric resection (ISR), especially the impact of inclusion of more juxtapositioned and intra‐anal tumours on oncological and functional outcomes. We compared the oncological and functional results of patients treated by total mesorectal excision and ISR for low rectal cancer over a 25‐year period. Method: This is a retrospective study from a single institution evaluating results of ISR over three periods: 1990–1998, 1999–2006 and 2007–2014. Patients treated by partial or total ISR, with or without neoadjuvant chemoradiotherapy, for low rectal cancer (≤ 6 cm from the anal verge) were included. We compared postoperative morbidity, quality of surgery and oncological and functional outcomes in the time periods studied. Results: Of 813 patients operated on for low rectal cancer, 303 had ISR. Tumour stage did not differ; however, the distance of the tumour from the anorectal junction decreased from 1 to 0 cm ( P  < 0.001) and the distal resection margin shortened from 25 to 10 mm ( P  < 0.001) from 1990 to 2014. The postoperative morbidity and quality of surgery did not change significantly over time. The 5‐year local recurrence (4.3% vs 5.9%  vs 3.5%; P  = 0.741) and disease‐free survival (72%  vs 71%  vs 75%; P  = 0.918) did not differ between the three time periods. Functional results improved during the last period; however, overall 42% of patients experienced major bowel dysfunction. Conclusion: Pushing the envelope of sphincter‐saving resection in ultra‐low rectal cancer reaching or invading the anal sphincter did not compromise oncological and functional outcomes. The main limitation of the ISR procedure appears to be functional rather than oncological, suggesting that bowel rehabilitation programmes should be developed.